How much monitoring is needed to reliably track progress towards genetic diversity targets? - Katherine Hébert; Laura Pollock; Sean Hoban (Biological Conservation, 2026)

Species Loss Scenarios Identify Canada's Northern Ecosystems as Disproportionately Vulnerable - Isaac Eckert; Dominique Caron; Laura J. Pollock (Journal of Biogeography, 2026)
Aim Amid ongoing and accelerating global change, predicting the ecological consequences of future species loss is important for prioritising conservation actions to protect biodiversity. Species richness has long been thought to protect communities from species loss by providing ecological redundancy, whereby the loss of any one species hardly impacts the integrity of the wider community due to overlap in species' ecological roles. However, the extent to which species richness will buffer the impacts of future species loss remains unclear due to concurrent variation in both the distribution and ecological roles of species likely to be lost. Location Canada. Taxon Terrestrial vertebrates. Methods To understand how future species loss threatens ecosystems and whether species richness mitigates this threat, we simulated the loss of imperilled taxa from Canadian ecosystems across spatial scales and measured the extent to which community functional and interaction (predator–prey) diversity, two important components of ecosystem integrity, declined. Results We report that, despite harbouring far fewer species at risk, northern ecosystems are disproportionately vulnerable, whereby the loss of imperilled taxa could result in up to 25% and 20% declines in functional and interaction diversity, respectively. Surprisingly, despite high species richness, some southern ecosystems containing high numbers of imperilled taxa were also vulnerable, indicating that richness alone is likely insufficient at predicting community vulnerability to species loss. Main Conclusions Together, these findings demonstrate the need to account for future species loss when evaluating the vulnerability of Earth's ecosystems and highlight the importance of conserving species at risk, specifically in northern communities where they potentially play outsized roles in structuring and maintaining the integrity of ecosystems.

Overcoming the disconnect between species interaction networks and biodiversity conservation - Gabriel Dansereau; João Braga; Gentile Francesco Ficetola; Núria Galiana; Dominique Gravel; Luigi Maiorano; José M. Montoya; Louise O’Connor; Laura Pollock; Wilfried Thuiller; Timothée Poisot; Ceres Barros (Trends in Ecology & Evolution, 2025)

No species left behind: borrowing strength to map data-deficient species - Shubhi Sharma; Kevin Winner; Laura J. Pollock; James T. Thorson; Jussi Mäkinen; Cory Merow; Eric J. Pedersen; Kalkidan F. Chefira; Julia M. Portmann; Fabiola Iannarilli; Sara Beery; Riccardo de Lutio; et al. (Trends in Ecology & Evolution, 2025)

Traits, Threats, and Popularity Explain Extinction Risk of Birds Globally - Janaína de Andrade Serrano; Lars Iversen; Laura J. Pollock (Global Ecology and Biogeography, 2025)
Aim This study aims to understand how biological traits, human‐induced threats, and species popularity interact to influence the extinction risk of bird species globally. We seek to improve the accuracy of extinction risk assessments and inform conservation strategies. Location Global. Time Period Current. Major Taxa Studied Birds. Methods We predict extinction risk for bird species globally based on relevant biological traits, threats (based on the IUCN Red List), and species popularity estimated from Google search frequency using a Bayesian hierarchical phylogenetic model. Results We find that biological traits, human‐induced threats, and species popularity all explain extinction risk. Some interactions are important (e.g., larger species are more likely threatened by hunting and small‐ranged and migratory species are more threatened by agriculture). We also find that more popular species are more likely to be listed as at risk than unpopular species with similar traits and threats. Main Conclusions Our study highlights the need for incorporating biological traits, anthropogenic threats and human bias into extinction risk assessments. These factors interact in complex ways, influencing the vulnerability of bird species. By accounting for these interactions, conservation efforts can be more effectively targeted to protect species with the highest risk.

Trophic Interactions Are Key to Understanding the Effects of Global Change on the Distribution and Functional Role of the Brown Bear - Pablo M. Lucas; Wilfried Thuiller; Lauren Talluto; Ester Polaina; Jörg Albrecht; Nuria Selva; Marta De Barba; Vincenzo Penteriani; Maya Guéguen; Niko Balkenhol; Trishna Dutta; Ancuta Fedorca; et al. (Global Change Biology, 2025)
Biotic interactions are expected to influence species' responses to global changes, but they are rarely considered across broad spatial extents. Abiotic factors are thought to operate at larger spatial scales, while biotic factors, such as species interactions, are considered more important at local scales within communities, in part because of the knowledge gap on species interactions at large spatial scales (i.e., the Eltonian shortfall). We assessed, at a continental scale, (i) the importance of biotic interactions, through food webs, on species distributions, and (ii) how biotic interactions under scenarios of climate and land‐use change may affect the distribution of the brown bear ( Ursus arctos ). We built a highly detailed, spatially dynamic, and empirically sampled food web based on the energy contribution of 276 brown bear food species from different taxa (plants, vertebrates, and invertebrates) and their ensemble habitat models at high resolution across Europe. Then, combining energy contribution and predicted habitat of food species, we modelled energy contribution across space and included these layers within Bayesian‐based models of the brown bear distribution in Europe. The inclusion of biotic interactions considerably improved our understanding of brown bear distribution at large (continental) scales compared with Bayesian models including only abiotic factors (climate and land use). Predicted future range shifts, which included changes in the distribution of food species, varied greatly when considering various scenarios of change in biotic factors, providing a warning that future indirect climate and land‐use change are likely to have strong but highly uncertain impacts on species biogeography. Our study confirmed that advancing our understanding of ecological networks of species interactions will improve future projections of biodiversity change, especially for modelling species distributions and their functional role under climate and land‐use change scenarios, which is key for effective conservation of biodiversity and ecosystem services.

Tempo and mode of diversification of the red devil spiders (Araneae: Dysderidae) of the Canary Islands - Adrià Bellvert; Laura J. Pollock; Antigoni Kaliontzopoulou; Miquel A. Arnedo (Zoologica Scripta, 2025)
The study of adaptive radiations has shed light on our current understanding of evolution. However, previous studies examining the mode in which species diversified, how diversification rates varied, and how ecological specialisation affected these processes have found few different results across different taxa and geographic and ecological systems, showing how complex this process is. To gain a more complete picture of how species evolve, additional model systems that encompass alternative ecological requirements are needed. Here, we present the results of a study aimed at unravelling the diversification mode and evolutionary drivers of the spider genus Dysdera , the red devil spiders, endemic to the Canary Islands. These species exhibit remarkable phenotypic variability in their mouthparts, which has been related to different levels of specialisation in the predation of isopods. We explored patterns of lineage diversification and assessed the role of trophic specialisation as a driver of species diversification. Additionally, we used climatic variables, occurrence data and morphological information to unravel the underlying mode of speciation by means of joint species distribution models and age‐range correlation methods. Our results reveal that red devil spiders underwent an early burst of diversification, followed by a slowdown of diversification rates, which is a hallmark of adaptive radiation. We also found evidence that the trophic morphology shaped diversification, with specialist species exhibiting higher rates of diversification. Finally, our analyses suggest that speciation occurred mostly in allopatry, with subsequent secondary sympatry following range expansion.

Five recommendations to fill the blank space in indicators at local and short-term scales - Katherine Hébert; Maximiliane Jousse; Janaína Serrano; Dirk Nikolaus Karger; F. Guillaume Blanchet; Laura J. Pollock (Biological Conservation, 2025)

Linking biodiversity, ecosystem function, and Nature’s contributions to people: a macroecological energy flux perspective - Ana Carolina Antunes; Emilio Berti; Ulrich Brose; Myriam R. Hirt; Dirk N. Karger; Louise M.J. O’Connor; Laura J. Pollock; Wilfried Thuiller; Benoit Gauzens (Trends in Ecology & Evolution, 2024)

Trait‐matching models predict pairwise interactions across regions, not food web properties - Dominique Caron; Ulrich Brose; Miguel Lurgi; F. Guillaume Blanchet; Dominique Gravel; Laura J. Pollock (Global Ecology and Biogeography, 2024)
Aim Food webs are essential for understanding how ecosystems function, but empirical data on the interactions that make up these ecological networks are lacking for most taxa in most ecosystems. Trait‐based models can fill these data gaps, but their ability to do so has not been widely tested. We test how well these models can extrapolate to new ecological communities both in terms of pairwise predator–prey interactions and higher level food web attributes (i.e. species position, food web‐level properties). Location Canada, Europe, Tanzania. Time Period Current. Major Taxa Studied Terrestrial vertebrates. Methods We train trait‐based models of pairwise trophic interactions on four independent vertebrate food webs (Canadian tundra, Serengeti, alpine south‐eastern Pyrenees and Europe) and evaluate how well these models predict pairwise interactions and network properties of each food web. Results We find that, overall, trait‐based models predict most interactions and their absence correctly. Performance was best for training and testing on the same food web (AUC > 0.90) and declined with environmental and phylogenetic distances with the strongest loss of performance for the tundra‐Serengeti ecosystems (AUC > 0.75). Network metrics were less well‐predicted than single interactions by our models with predicted food webs being more connected, less modular, and with higher mean trophic levels than observed. Main Conclusions Theory predicts that the variability observed in food webs can be explained by differences in trait distributions and trait‐matching relationships. Our finding that trait‐based models can predict many trophic interactions, even in contrasting environments, adds to the growing body of evidence that there are general constraints on interactions and that trait‐based methods can serve as a useful first approximation of food webs in unknown areas. However, food webs are more than the sum of their parts, and predicting network attributes will likely require models that simultaneously predict individual interactions and community constraints.

Novel community data in ecology-properties and prospects - Florian Hartig; Nerea Abrego; Alex Bush; Jonathan M. Chase; Gurutzeta Guillera-Arroita; Mathew A. Leibold; Otso Ovaskainen; Loïc Pellissier; Maximilian Pichler; Giovanni Poggiato; Laura Pollock; Sara Si-Moussi; et al. (Trends in Ecology & Evolution, 2024)

Vulnerability of terrestrial vertebrate food webs to anthropogenic threats in Europe - Louise M. J. O'Connor; Francesca Cosentino; Michael B. J. Harfoot; Luigi Maiorano; Chiara Mancino; Laura J. Pollock; Wilfried Thuiller (Global Change Biology, 2024)
Vertebrate species worldwide are currently facing significant declines in many populations. Although we have gained substantial knowledge about the direct threats that affect individual species, these threats only represent a fraction of the broader vertebrate threat profile, which is also shaped by species interactions. For example, threats faced by prey species can jeopardize the survival of their predators due to food resource scarcity. Yet, indirect threats arising from species interactions have received limited investigation thus far. In this study, we investigate the indirect consequences of anthropogenic threats on biodiversity in the context of European vertebrate food webs. We integrated data on trophic interactions among over 800 terrestrial vertebrates, along with their associated human‐induced threats. We quantified and mapped the vulnerability of various components of the food web, including species, interactions, and trophic groups to six major threats: pollution, agricultural intensification, climate change, direct exploitation, urbanization, and invasive alien species and diseases. Direct exploitation and agricultural intensification were two major threats for terrestrial vertebrate food webs: affecting 34% and 31% of species, respectively, they threaten 85% and 69% of interactions in Europe. By integrating network ecology with threat impact assessments, our study contributes to a better understanding of the magnitude of anthropogenic impacts on biodiversity.

Indicators to monitor the status of the tree of life - Rikki Gumbs; Abhishek Chaudhary; Barnabas H. Daru; Daniel P. Faith; Félix Forest; Claudia L. Gray; Aida Kowalska; Who‐Seung Lee; Roseli Pellens; Sebastian Pipins; Laura J. Pollock; James Rosindell; et al. (Conservation Biology, 2023)
Following the failure to fully achieve any of the 20 Aichi biodiversity targets, the future of biodiversity rests in the balance. The Convention on Biological Diversity's Kunming–Montreal Global Biodiversity Framework (GBF) presents the opportunity to preserve nature's contributions to people (NCPs) for current and future generations by conserving biodiversity and averting extinctions. There is a need to safeguard the tree of life—the unique and shared evolutionary history of life on Earth—to maintain the benefits it bestows into the future. Two indicators have been adopted within the GBF to monitor progress toward safeguarding the tree of life: the phylogenetic diversity (PD) indicator and the evolutionarily distinct and globally endangered (EDGE) index. We applied both to the world's mammals, birds, and cycads to show their utility at the global and national scale. The PD indicator can be used to monitor the overall conservation status of large parts of the evolutionary tree of life, a measure of biodiversity's capacity to maintain NCPs for future generations. The EDGE index is used to monitor the performance of efforts to conserve the most distinctive species. The risk to PD of birds, cycads, and mammals increased, and mammals exhibited the greatest relative increase in threatened PD over time. These trends appeared robust to the choice of extinction risk weighting. EDGE species had predominantly worsening extinction risk. A greater proportion of EDGE mammals (12%) had increased extinction risk compared with threatened mammals in general (7%). By strengthening commitments to safeguarding the tree of life, biodiversity loss can be reduced and thus nature's capacity to provide benefits to humanity now and in the future can be preserved.

Addressing the Eltonian shortfall with trait‐based interaction models - Dominique Caron; Luigi Maiorano; Wilfried Thuiller; Laura J. Pollock (Ecology Letters, 2022)
We have very limited knowledge of how species interact in most communities and ecosystems despite trophic relationships being fundamental for linking biodiversity to ecosystem functioning. A promising approach to fill this gap is to predict interactions based on functional traits, but many questions remain about how well we can predict interactions for different taxa, ecosystems and amounts of input data. Here, we built a new traits‐based model of trophic interactions for European vertebrates and found that even models calibrated with 0.1% of the interactions (100 out of 71 k) estimated the full European vertebrate food web reasonably well. However, predators were easier to predict than prey, especially for some clades (e.g. fowl and storks) and local food web connectance was consistently overestimated. Our results demonstrate the ability to rapidly generate food webs when empirical data are lacking—an important step towards a more complete and spatially explicit description of food webs.

Environmental and anthropogenic constraints on animal space use drive extinction risk worldwide - Myriam R. Hirt; Andrew D. Barnes; Alessandro Gentile; Laura J. Pollock; Benjamin Rosenbaum; Wilfried Thuiller; Marlee A. Tucker; Ulrich Brose (Ecology Letters, 2021)
Animals require a certain amount of habitat to persist and thrive, and habitat loss is one of the most critical drivers of global biodiversity decline. While habitat requirements have been predicted by relationships between species traits and home‐range size, little is known about constraints imposed by environmental conditions and human impacts on a global scale. Our meta‐analysis of 395 vertebrate species shows that global climate gradients in temperature and precipitation exert indirect effects via primary productivity, generally reducing space requirements. Human pressure, however, reduces realised space use due to ensuing limitations in available habitat, particularly for large carnivores. We show that human pressure drives extinction risk by increasing the mismatch between space requirements and availability. We use large‐scale climate gradients to predict current species extinction risk across global regions, which also offers an important tool for predicting future extinction risk due to ongoing space loss and climate change.

Variants in GCNA, X-linked germ-cell genome integrity gene, identified in men with primary spermatogenic failure - Jimmaline J. Hardy; Margot J. Wyrwoll; William Mcfadden; Agnieszka Malcher; Nadja Rotte; Nijole C. Pollock; Sarah Munyoki; Maria V. Veroli; Brendan J. Houston; Miguel J. Xavier; Laura Kasak; Margus Punab; et al. (Human Genetics, 2021)

Dos and don'ts when inferring assembly rules from diversity patterns - Tamara Münkemüller; Laure Gallien; Laura J. Pollock; Ceres Barros; Marta Carboni; Loïc Chalmandrier; Florent Mazel; Karel Mokany; Cristina Roquet; Jan Smyčka; Matthew V. Talluto; Wilfried Thuiller (Global Ecology and Biogeography, 2020)
Aim More than ever, ecologists seek to understand how species are distributed and have assembled into communities using the “filtering framework”. This framework is based on the hypothesis that local assemblages result from a series of abiotic and biotic filters applied to regional species pools and that these filters leave predictable signals in observed diversity patterns. In theory, statistical comparisons of expected and observed patterns enable data‐driven tests of assembly processes. However, so far this framework has fallen short in delivering generalizable conclusions, challenging whether (and how) diversity patterns can be used to characterize and understand underlying assembly processes better. Methods By synthesizing the previously raised critiques and suggested solutions in a comprehensive way, we identify 10 pitfalls that can lead to flawed interpretations of α‐diversity patterns, summarize solutions developed to circumvent these pitfalls and provide general guidelines. Results We find that most issues arise from an overly simplistic view of potential processes that influence diversity patterns, which is often motivated by practical constraints on study design, focal scale and methodology. We outline solutions for each pitfall, such as methods spanning over spatial, environmental or phylogenetic scales, and suggest guidelines for best scientific practices in community ecology. Among key future challenges are the integration of mechanistic modelling and multi‐trophic interactions. Main conclusions Our conclusion is that the filtering framework still holds promise, but only if researchers successfully navigate major pitfalls, foster the integration of mechanistic modelling and multi‐trophic interactions and directly account for uncertainty in their conclusions.

Productivity begets less phylogenetic diversity but higher uniqueness than expected - Wilfried Thuiller; Dominique Gravel; Gentile Francesco Ficetola; Sébastien Lavergne; Tamara Münkemüller; Laura J. Pollock; Niklaus E. Zimmermann; Florent Mazel (Journal of Biogeography, 2020)
Aim The positive effect of primary productivity on animal species richness is one of the most conspicuous ecological features on Earth. However, less is known about the relationship between ecosystems primary productivity and the evolutionary history of biota. Here, we analyse how global primary productivity relates to the phylogenetic structure of vertebrate assemblages, and to the distribution of the most distinct lineages and recently diversified clades. Location Global. Taxon Amphibians, birds and mammals. Methods We calculated relative phylogenetic diversity (i.e. phylogenetic diversity corrected for species richness), standardized effect size of the richness of top 25% evolutionary distinct species and of top 25% species‐level lineage diversification rates. We related these three metrics to mean net primary productivity (NPP) at the global scale, and for each zoogeographic region. We also tested the influence of the spatial scaling of species pool on the overall analyses (global, hemispheric and zoogeographic regions‐based species pools). Results Phylogenetic diversity (corrected for species richness) of the three taxa decreases with NPP (in contrast with species richness) and varies considerably in space. High productivity sites harbour more closely related species than low productivity sites consistently across zoogeographic zones. However, the phylogenetically most distinct species are also found in high productivity sites, while the top most rapidly diversifying lineages are found in the least productive sites. Modifying the spatial extent of the species pool did not affect the results much. Conclusions Benign conditions in high productivity sites (a) result in denser niche packing and thus allow for the coexistence of many closely‐related species and (b) protect the persistence of evolutionary distinct species. Low productivity sites may harbour fewer, more distinct and temporarily more variable niches that allow maintenance of unique lineages for longer periods of time.

Unveiling the food webs of tetrapods across Europe through the prism of the Eltonian niche - Louise M. J. O’Connor; Laura J. Pollock; João Braga; Gentile Francesco Ficetola; Luigi Maiorano; Camille Martinez‐Almoyna; Alessandro Montemaggiori; Marc Ohlmann; Wilfried Thuiller (Journal of Biogeography, 2020)
Aim Despite recent calls for integrating interaction networks into the study of large‐scale biodiversity patterns, we still lack a basic understanding of the functional characteristics of large interaction networks and how they are structured across environments. Here, building on recent advances in network science around the Eltonian niche concept, we aim to characterize the trophic groups in a large food web, and understand how these trophic groups vary across space. Location Europe and Anatolia. Taxon Tetrapods (1,136 species). Methods We combined an expert‐based metaweb of all European tetrapods with their spatial distributions and biological traits. To understand the functional structure of the metaweb, we first used a stochastic block model to group species with similar Eltonian niches, and then analysed these groups with species’ functional traits and network metrics. We then combined these groups with species distributions to understand how trophic diversity varies across space, in function of the environment, and between the European ecoregions. Results We summarized the 1,136 interacting species within the metaweb into 46 meaningful trophic groups of species with a similar role in the metaweb. Specific aspects of the ecology of species, such as their activity time, nesting habitat and diet explained these trophic groups. Across space, trophic diversity was driven by both biotic and abiotic factors (species richness, climate and primary productivity), and the representation of trophic groups differed among European ecoregions. Main conclusions We have characterized the Eltonian niche of species in a large food web, both in terms of species interactions and functional traits, and then used this to understand the spatial variation of food webs at a functional level, thus bringing together network science, functional ecology and biogeography. Our results highlight the need to integrate multiple aspects of species ecology in global change research. Further, our approach is strongly relevant for conservation biology as it could help predict the impact of species translocations on trophic diversity.

Spatial analyses of multi‐trophic terrestrial vertebrate assemblages in Europe - João Braga; Laura J. Pollock; Ceres Barros; Núria Galiana; José M. Montoya; Dominique Gravel; Luigi Maiorano; Alessandro Montemaggiori; Gentile Francesco Ficetola; Stéphane Dray; Wilfried Thuiller (Global Ecology and Biogeography, 2019)
Aim Although much has been said on the spatial distribution of taxonomic and phylogenetic diversity of vertebrates, how this diversity interacts in food webs and how these interactions change across space are largely unknown. Here, we analysed the spatial distribution of tetrapod food webs and asked whether the variation in local food web structure is driven by random processes or by natural and anthropogenic factors. Location Europe. Time period Present. Major taxa studied Tetrapods. Methods We combined an expert‐based food web (1,140 species and 70,601 links) of all European tetrapods with their respective spatial distributions. We mapped 17 different food web metrics representing complexity, chain length, vertical diversity and diet strategy across Europe and tested whether their distribution reflects the spatial structure of species richness using a null model of food web structure. To avoid multicollinearity issues, we defined composite descriptors of food web structure that we related to a set of environmental layers summarizing both natural and anthropogenic influences and tested their relative importance in explaining the spatial distribution of European terrestrial vertebrate food webs. Results Of the 17 metrics, 10 showed a non‐random spatial distribution across Europe and could be summarized along two major axes of variation in food web structure. The first was related to species richness, mean trophic level and the proportion of intermediate species, whereas the second was related to the connectance and proximity of species within the web. Both descriptors varied with latitudinal gradient. The best descriptors of food web structure were mean annual temperature and seasonality (negatively correlated with the first axis), and human footprint (positively correlated with the second axis). Main conclusions We demonstrate the importance of climate and anthropogenic pressure in shaping the spatial structure of European tetrapod food webs.

Functional traits modulate the response of alien plants along abiotic and biotic gradients - Marta Carboni; Irene Calderon‐Sanou; Laura Pollock; Cyrille Violle; Wilfried Thuiller (Global Ecology and Biogeography, 2018)
Aim It is widely recognized that the prediction of invasion success at large biogeographical scales requires jointly accounting for alien species traits and local community filters, such as abiotic conditions, biotic interactions and propagule pressure. Despite this recognition, interactions between traits and community filters are generally neglected. Here, we aim to address this limitation by developing a hierarchical framework that builds on trait‐based theory to model occurrences of alien species as a function of spatially explicit variables, filtering invasions and their interactions with species traits. Location Herbaceous communities throughout France. Time period c . 1960–2012 (mostly after 1990). Major taxa studied Herbaceous plants. Methods Based on a large dataset of >50,000 community plots, we built a multispecies hierarchical model of the distribution of the 10 most widespread alien plants in French grasslands. In this model, we explicitly account for how plant height, specific leaf area (SLA) and seed mass affect the occurrence of alien species along gradients of human pressure, environmental conditions and native community composition. Finally, we contrast the results to native species responses along the same gradients. Results We show that two out of three traits significantly modulate the responses of species along these broad gradients. Alien plants with exploitative traits (i.e., tall and with high SLA) were less dependent on human pressure, more efficient in resource‐rich environments and better at avoiding competition from native species. These trait–gradient interactions were often unique to alien plants (e.g., human pressure was important only for supporting alien species with low SLA), even though trait ranges of alien and native species were comparable. Ultimately, the modelling of trait–gradient interactions allows spatially explicit estimations of invasion risks by novel species with particular sets of traits. Main conclusions By taking the best from multispecies distribution modelling and trait‐based theory, our framework paves the way for a generalized mechanistic understanding of how traits influence the success of alien plants and their spatial distributions.

From species distributions to meta‐communities - Wilfried Thuiller; Laura J. Pollock; Maya Gueguen; Tamara Münkemüller (Ecology Letters, 2015)
The extent that biotic interactions and dispersal influence species ranges and diversity patterns across scales remains an open question. Answering this question requires framing an analysis on the frontier between species distribution modelling ( SDM ), which ignores biotic interactions and dispersal limitation, and community ecology, which provides specific predictions on community and meta‐community structure and resulting diversity patterns such as species richness and functional diversity. Using both empirical and simulated datasets, we tested whether predicted occurrences from fine‐resolution SDM s provide good estimates of community structure and diversity patterns at resolutions ranging from a resolution typical of studies within reserves (250 m) to that typical of a regional biodiversity study (5 km). For both datasets, we show that the imprint of biotic interactions and dispersal limitation quickly vanishes when spatial resolution is reduced, which demonstrates the value of SDM s for tracking the imprint of community assembly processes across scales.

Chloroplast DNA diversity associated with protected slopes and valleys for hybridizing Eucalyptus species on isolated ranges in south‐eastern Australia - Laura J. Pollock; Michael J. Bayly; Paul G. Nevill; Peter A. Vesk (Journal of Biogeography, 2013)
Aim To relate genetic diversity to topographic features and to investigate genetic interactions between Eucalyptus species in a local centre of endemism and diversity in south‐eastern Australia. Location Grampian Ranges, Victoria, Australia. Methods We documented chloroplast DNA (cpDNA) variation for a group of endemic Eucalyptus species ( E. serraensis, E. verrucata and E. victoriana ) that dominate rocky, high‐elevation ridgelines of the Grampian Ranges and for one closely‐related, widespread species ( E. baxteri ) occupying flanking slopes and valleys. We documented genetic patterns across the landscape using cpDNA microsatellites, and related them to topographic features (exposed west‐facing versus protected east‐facing slopes and valleys). We also determined the extent of local haplotype sharing between populations of endemic species and neighbouring E. baxteri downslope with cpDNA microsatellites, and haplotype sharing between the endemic group and more distantly related species ( E. obliqua , E. pauciflora and E. willisii ) with sequences of the J LA + chloroplast region. Results We detected 26 cpDNA microsatellite haplotypes in a relatively small area of c . 20 km × 50 km. Populations of E. baxteri on east‐facing slopes and valleys had greater cpDNA microsatellite diversity than E. baxteri and endemic species on exposed west‐facing slopes. Endemic species frequently shared chloroplast haplotypes with E. baxteri downslope. Sharing of J LA + haplotypes with species outside the endemic group was mostly restricted to E. victoriana , which had cpDNA more similar to the species from other sections of Eucalyptus ( E. obliqua , E. willisii and E. pauciflora ). Main conclusions Intensive sampling of related species on small isolated mountain ranges allowed us to relate genetic diversity to fine‐scale habitats and to document extensive local haplotype sharing between species. This study contributes to a general understanding of the environmental conditions that enable plant population persistence by linking concentrations of genetic diversity to particular habitats.